Clonality and distribution of clinical Ureaplasma isolates recovered from male patients and infertile couples in China. - Zhi Ruan; Ting Yang; Xinyan Shi; Yingying Kong; Xinyou Xie; Jun Zhang (PLoS ONE)
Ureaplasma spp. have gained increasing recognition as pathogens in both adult and neonatal patients with multiple clinical presentations. However, the clonality of this organism in the male population and infertile couples in China is largely unknown. In this study, 96 (53 U. parvum and 43 U. urealyticum) of 103 Ureaplasma spp. strains recovered from genital specimens from male patients and 15 pairs of infertile couples were analyzed using multilocus sequence typing (MLST)/expanded multilocus sequence typing (eMLST) schemes. A total of 39 sequence types (STs) and 53 expanded sequence types (eSTs) were identified, with three predominant STs (ST1, ST9 and ST22) and eSTs (eST16, eST41 and eST82). Moreover, phylogenetic analysis revealed two distinct clusters that were highly congruent with the taxonomic differences between the two Ureaplasma species. We found significant differences in the distributions of both clusters and sub-groups between the male and female patients (P < 0.001). Moreover, 66.7% and 40.0% of the male and female partners of the infertile couples tested positive for Ureaplasma spp. The present study also attained excellent agreement of the identification of both Ureaplasma species between paired urine and semen specimens from the male partners (k > 0.80). However, this concordance was observed only for the detection of U. urealyticum within the infertile couples. In conclusion, the distributions of the clusters and sub-groups significantly differed between the male and female patients. U. urealyticum is more likely to transmit between infertile couples and be associated with clinical manifestations by the specific epidemic clonal lineages.